2023
DOI: 10.1021/acsami.2c22086
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Dexter Energy Transfer through Modulating Donor Segments of Thermally Activated Delayed Fluorescence Assistant Dopants

Abstract: Device degradation in red hyperfluorescent organic light-emitting diodes is primarily caused by exciton energy loss due to Dexter energy transfer (DET) from a thermally activated delayed fluorescence (TADF) assistant dopant to a fluorescent dopant. In this work, the donor segments in the TADF assistant dopants were delicately modulated to suppress DET for high efficiency. The derived benzothienocarbazole donors were introduced to the TADF assistant dopants instead of carbazole, and they accelerated the reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, the 12BTCzTPN device showed slightly improved efficiency roll-off due to its higher rISC rate, which was attributed to the heavy-atom effect of the sulfur . Lee et al reported that red hyperfluorescent OLEDs fabricated with three benzothienocarbazole-based emitters (PLQY = 25–36%) showed slightly higher EQ E max values in the range of 12.3–14.7% compared to a carbazole counterpart (EQE max 11.3%) . These benzothienocarbazole-based derivatives also showed shorter DF lifetimes as compared to their nonsulfur TADF congeners.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the 12BTCzTPN device showed slightly improved efficiency roll-off due to its higher rISC rate, which was attributed to the heavy-atom effect of the sulfur . Lee et al reported that red hyperfluorescent OLEDs fabricated with three benzothienocarbazole-based emitters (PLQY = 25–36%) showed slightly higher EQ E max values in the range of 12.3–14.7% compared to a carbazole counterpart (EQE max 11.3%) . These benzothienocarbazole-based derivatives also showed shorter DF lifetimes as compared to their nonsulfur TADF congeners.…”
Section: Resultsmentioning
confidence: 99%
“…Benzothienocarbazoles are relatively unexplored donor systems for designing TADF emitters, ,,, and so it was of particular interest to isolate any potential heavy-atom effect of sulfur by comparison with the parent carbazole analogue Cz-CF3 . Due to the relatively weaker donor strength of Cz compared to TCz, 1 wt % zeonex films of Cz-CF3 showed deeper-blue emission compared to TCz-CF3 and with a relatively large Δ E ST of 0.15 eV (Figure d, Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…With the polycyclic aromatic hydrocarbon DBP as the fluorescent emitter hyperfluorescent 2BT12CzINN :DBP devices in a PBICT:DBTTP1 host had EQE max 14.7% and CIE(0.60, 0.39). 134 The EQE and the lifetime LT 90 of 41.8 h at L 0 3000 cd m −2 were improved compared to a reference 4CzTPN:DBP device (EQE max 11.3%; LT 90 27.8 h).…”
Section: Fused Carbazole Derivatives As Tadf Emittersmentioning
confidence: 86%
“…Donors of different chromophores, such as benzofurocarbazole and benzothienocarbazole, which are obtained by fusing carbazole with benzofuran or benzothiophene, have also been developed. [4][5][6] Recently, materials with improved rigidity, based on the v-DABNA backbone and known as HF materials, have been reported. 7,8 The second key principle involves conferring bipolar characteristics to maintain charge balance.…”
Section: Introductionmentioning
confidence: 99%